Saúde perinatal: baixo peso e classe social Perinatal health: low birth weight and social class - Antonio A. Moura da Silva; Marco Antonio Barbieri; Heloisa Bettiol; Creusa M.R. Dal Bó; Gérson Mucillo; Uilho Antonio Gomes (Universidade de São Paulo, 1991)
Estudou-se, em Ribeirão Preto, SP, Brasil, no período de 1º de junho de 1978 a 31 de maio de 1979, 98% do universo de nascidos vivos, totalizando 8.878 crianças nascidas de parto único. As taxas de baixo peso e de peso deficiente ao nascer foram de 7,5% e de 21,1%, respectivamente. A maioria dos nascimentos de baixo peso eram crianças a termo, 50,6%, representando casos de retardo de crescimento intra-uterino. A prevalência de baixo peso nas classes sociais foi de 3,2% na burguesia empresarial, 2,8% na burguesia gerencial, 3,9% na pequena burguesia, 7,0% no proletariado e 9,5% no subproletariado, o que demonstra uma profunda disparidade. Definindo-se o baixo peso como menor ou igual a 2.500 gramas e comparando os resultados alcançados (8,3%) com os de outro estudo clássico (8,7%), observou-se que não houve redução estatisticamente significativa na prevalência de baixo peso em Ribeirão Preto, no intervalo de uma década. A survey was carried out in Ribeirão Preto, S. Paulo State, Brazil, between June 1978 and May 1979 with a view to studying the prevalence of low birth weight and its occurrence among different social classes. Data were collected from 8,878 singleton live births in eight maternity hospitals, accounting for 98% of all births in the area. Social classes were determinated by the use of a model proposed by Singer and modified for epidemiological purposes by Barros. Out of the 8,878 births, 660 (7.5%) were of low birth weight. The prevalence of deficient weight at birth (between 2,500 and 2,999 grams) was of 21.1%. Analysis indicated that 50.6% of children with low birth weight were at term and the majority of them suffered form intrauterine growth retardation. The prevalence of low birth weight according to social class was seen to be lower in the bourgeoisie classes (ranging from 2.8% to 3.9%) and higher in working classes (from 7% up to 9.5%). Low birth weight (defined as < 2,500 grams) was used for purposes of comparison with other previous surveys. The percentage was lower in this study (8.3%) than that found in the Interamerican Investigation of Mortality in Childhood (8.7%), carried out in 1968-70. No statistically significant differences in the percentage of low birth weight were found in the case of Ribeirão Preto when these two surveys were compared.